Pakistan - "Cohen, Stephen Philip" (New Delhi, 2004)
Many observers have characterized Pakistan as a failed state, or even a rogue state. This book examines the factors contributing to state failure and asks whether the dual identities of Pakistan, created as a homeland for Indian muslims and as the world's first modern Islamic state, are viable in today's world
Keywords: Pakistan-politics and governemnt